Plant-Based Milks: Coconut - Celia Andreo; Daniela Rivero-Mendoza; Wendy J Dahl (EDIS)
Plant-based alternatives to cow's milk have become a rising trend. Factors that may steer consumers toward nondairy milk alternatives include adherence to a vegan diet, lactose intolerance, allergy to cow's milk, or simply preference. Coconut milk is one of the many varieties of plant-based milk. Whether you are considered switching to or have already begun purchasing a plant-based milk, the purpose of this new 4-page guide is to inform you on the nutrient content of coconut milk and its potential health benefits and risks. Written by Celia Andreo, Daniela Rivero-Mendoza, and Wendy J. Dahl, and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs411